EFEKTIVITAS PENGGUNAAN QUIZIZZ SEBAGAI ALAT EVALUASI PADA TEMA 5 SUBTEMA 1 KELAS V SDN 173529 TAMPAHAN KECAMATAN TAMPAHAN - Day, Gheeta Valentini Day Valentini; Simanjuntak, Sorta; Mailani, Elvi; Rozi, Fahrur Rozi; Mustika Aulia, Sri (Universitas Negeri Medan, 2024)
The problem underlying this research is that the evaluation of student learning outcomes at SDN 173529 Tampahan has not been in accordance with the times, boring so that students do not respond well and tend to be less interested in completing the evaluation of learning outcomes. The purpose of this study is to determine the effectiveness of using Quizizz as an evaluation tool to improve the learning outcomes of grade 5 students of Sesmester 2 (Even) T.A 2023/ 2024 at SDN 173529 Tampahan. This research is a quantitative research with quasi-experimental methods. The subject of class V students is 20 students. The research instrument consists of (1) Observation Sheets related to the implementation of evaluations carried out by teachers. (2) Test using Quiziz. Data analysis techniques are carried out descriptively and continued with paired simpl t-test, which is a paired data difference test. Based on descriptive statistical data analysis, the average prestest was 67 and the average value of posttest results was 87.25. Furthermore, the hypothesis test through the t-test obtained the calculated t value is 4,28 > 1,72 t table, alpha value 0.05 with a difference of n-1. So Ho was rejected meaning: The effectiveness of using quizizz as a significant (high) evaluation tool for student learning outcomes in learning Theme 5 Subtheme 1 grade 5 at SDN 173529 Tampahan, Kec, Tampahan T.A 2023/ 2024. Significant with a confidence level of 95%. Keywords: Evaluation,Evaluation Tool,Quiziz, Learning Outcomes